2007
DOI: 10.1016/j.molcel.2006.12.020
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Regulates HIV-1 Transcription by Both Proteolytic and Nonproteolytic Mechanisms

Abstract: Although the proteasome facilitates transcription from several yeast promoters, it is unclear if its role is proteolytic or which subunits are involved. We show that the proteasome regulates the HIV-1 promoter in both proteolytic and nonproteolytic modes. In the absence of transcription factor, Tat, proteasome was associated with promoter and coding regions, and its proteolytic activity regulated the level of basal transcription emanating from the promoter. Tat switched the proteasome to a nonproteolytic mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 29 publications
8
76
1
Order By: Relevance
“…Previous studies have demonstrated that the base, base-like complex, and RP function in transcription, independent of the proteolytic function of the proteasome, implying that the proteasome subcomplexes may have specific roles in cells [43][44][45] . However, our results suggest that the 26S proteasome is a very stable complex, and that free base, RP, and subunits are not present at detectable levels anywhere in the cell, at least under normal culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the base, base-like complex, and RP function in transcription, independent of the proteolytic function of the proteasome, implying that the proteasome subcomplexes may have specific roles in cells [43][44][45] . However, our results suggest that the 26S proteasome is a very stable complex, and that free base, RP, and subunits are not present at detectable levels anywhere in the cell, at least under normal culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For viral RNA quantification, the following primers and probe amplifying tat/rev/nef mRNA were used: forward 5Ј-GGATCTGTCTCTGTCTCTCTCTCCACC-3Ј, reverse 5Ј-ACAGTCAGACTCATCAAGTTTCTCTATCAAAGCA-3Ј, and the dual-labeled fluorescent probe FAM 5Ј-TTCCTTCG-GGCCTGTCGGGTCCC-3Ј TAMRA (26). TAR transcripts were quantified with the following primers and probe: forward 5Ј-GGGTCTCTCTGGTTAGA-3Ј, reverse 5Ј-GGGTTCCCT-AGTTAG-3Ј, and the probe that is complementary to the TAR loop region of the HIV-1 LTR and also dual-labeled, FAM 5Ј-GCCTGGGAGCTCTCTGG-3Ј TAMRA (27,28).…”
Section: Cells-tzm-bl and Hek293t Cells (Aidsmentioning
confidence: 99%
“…This proteasomal subcomplex, which has been called APIS or the 19 S base (we will use the latter term here), is recruited to GAL promoters by Gal4 and is important for efficient promoter escape and elongation (7,8). The proteasomal ATPases are also important for efficient promoter escape in other systems (9). Although the precise mechanistic basis of this effect has yet to be determined, a plausible model is that the protein unfolding activity of the ATPases, when uncoupled from proteolysis, acts to somehow remodel the preinitiation complex into an elongation complex, a process that is known to require many alterations in protein-protein and protein-nucleic acid interactions (10).…”
mentioning
confidence: 99%